Cirrhotic Cardiomyopathy: Does it Contribute to Chronic Fatigue and Decreased Health-Related Quality of Life in Cirrhosis? - Nigel Girgrah; Graham Reid; Shona MacKenzie; Florence Wong (Canadian Journal of Gastroenterology)
Diminished health-related quality of life (HRQoL) and fatigue have been reported in patients with cirrhosis. The presence of cirrhotic cardiomyopathy and the attendant poor cardiac response to physical stress may affect HRQoL and contribute to fatigue in these patients.